Unraveling Determinants of Risk Culture in Islamic Banking: Perspectives from Importance-Performance Matrix Analysis - Sebayang, Saimara A.M.; Sukiman, Sukiman; Agus, Rizal (IQTISHODUNA: Jurnal Ekonomi Islam, 2024)
This study aims to enhance our understanding of the determinants of risk culture within Islamic Banking and provide valuable guidance to management for strengthening it. Using an explanatory research design, quantitative methodology, and importance-performance matrix analysis, we distributed Google Forms to 400 employees via email and WhatsApp. The pivotal determinants of risk culture identified in the study are organization, competency, and leadership. Risk culture, which includes organizational principles, norms, frameworks, and guidelines shaping risk management, is primarily determined by the organization. The research emphasizes the crucial role of leadership in establishing, cultivating, and implementing a risk culture, highlighting its substantial impact on upholding risk management standards. Underlining the pivotal significance of organization and leadership is essential for strengthening risk culture in Islamic Banking. This involves enhancing organizational capabilities through core values, regulatory frameworks, and a steadfast commitment to robust risk management standards. Leadership in Islamic banking holds a critical position, providing unwavering support for minimizing errors, fostering operational consistency, and maintaining a resolute track record of achievements. By emphasizing these three interrelated dimensions, the study contributes to the advancement of sustainable and resilient Islamic banking practices on a global scale.